Fluorescent non transgenic schistosoma to decipher host-parasite phenotype compatibility - Duval, David; Poteaux, Pierre; Gourbal, Benjamin; Rognon, Anne; Augusto, Ronaldo De Carvalho (Frontiers in Immunology, 2023)
Schistosomiasis is considered as a significant public health problem, imposing a deeper understanding of the intricate interplay between parasites and their hosts. Unfortunately, current invasive methodologies employed to study the compatibility and the parasite development impose limitations on exploring diverse strains under various environmental conditions, thereby impeding progress in the field. In this study, we demonstrate the usefulness for the trematode parasite Schistosma mansoni, leveraging a fluorescence-imaging-based approach that employs fluorescein 5-chloromethylfluorescein diacetate (CMFDA) and 5-chloromethylfluorescein diacetate (CMAC) as organism tracker for intramolluscan studies involving the host snail Biomphalaria glabrata. These probes represent key tools for qualitatively assessing snail infections with unmatched accuracy and precision. By monitoring the fluorescence of parasites within the snail vector, our method exposes an unprecedented glimpse into the host-parasite compatibility landscape. The simplicity and sensitivity of our approach render it an ideal choice for evolutionary studies, as it sheds light on the intricate mechanisms governing host-parasite interactions. Fluorescent probe-based methods play a pivotal role in characterizing factors influencing parasite development and compatibility phenotypes, paving the way for innovative, effective, and sustainable solutions to enhance our understanding of host-parasite immunobiological interactions and compatibility